2012
DOI: 10.1159/000345387
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ultrasound during Intrauterine Insemination in Unexplained Infertility May Improve Pregnancy Outcomes

Abstract: Objective: To investigate the role of ultrasound guidance in intrauterine insemination (IUI). Materials and Methods: A retrospective study was conducted. The data was collected from the records of 197 couples with unexplained infertility who underwent IUI with a total of 267 IUI cycles in the in vitro fertilization center of our hospital between January 2009 and December 2010. Results: Of the 267 IUI cycles, 145 were carried out as US-guided, while 122 cycles IUI were performed with a blind procedure. In the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Our study strongly agree with the study that done by (11) on 51 infertile women, who found that UBP score above 15 have 100% pregnancy rate. While in women with UBP scores of <12 pregnancy rate was 0%.…”
Section: Comparison Total Uterine Biophysical Profile Between Pregnan...supporting
confidence: 93%
“…Our study strongly agree with the study that done by (11) on 51 infertile women, who found that UBP score above 15 have 100% pregnancy rate. While in women with UBP scores of <12 pregnancy rate was 0%.…”
Section: Comparison Total Uterine Biophysical Profile Between Pregnan...supporting
confidence: 93%
“…In contrast with the study done by Ramón et al [15], recently published trial done by Oztekin et al indicates there might be an increase in the pregnancy rates with the IUI procedure under US guidance [18]. Through this retrospective study, randomization was provided with applying IUI under US guidance to those patients who had a full bladder, and blindly IUI application to those who had an empty bladder.…”
Section: Discussionmentioning
confidence: 87%
“…However in a low dose step up protocol, there is no need for such an effort they did not use cetrorelix or rLH. IUI was cancelled if three or more follicles developed and they were excluded from the study since ratio of multiple pregnancy increase in these patients [18], while Ramón et al [15] used five follicles as the cycle limit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Ramon et al [21] published an RCT with 73 patients to ascertain whether ultrasound guidance during insemination in IUI treatment could increase the pregnancy rate, and concluded that ultrasound did not produce better results than blind insemination, as the pregnancy rates were similar in both groups, which is in accordance with our results. Three years later, Oztekin et al [22] conducted a retrospective study of 267 IUI cycles in patients with unexplained infertility and concluded that ultrasound-guided IUI increased the pregnancy rates and reduced the frequency of difficult IUI. However, that was a retrospective study and therefore needs to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%